Culture and author’s personality in the literary text: A rereading of Abubakar Imam’s Magana jari ce - Shuaibu Hassan (Studies in African Languages and Cultures, 2023)
The article is an attempt to look at the literary text as a manifestation of the author’s personality and cultural background. The analysis concerns the book Magana jari ce ‘Wisdom is an asset’, containing stories from the native Hausa tradition and foreign motifs, adapted by the author, Abubakar Imam, for the Hausa text. The analysis is to demonstrate links between author’s personality and cultural background in creative adaptation of the stories in the book. It is argued here that from the eighty-four stories in Magana jari ce, in most of them the scenery, characters, and the way they are presented are motivated by the author’s personal experiences, which also show the values and moral standards recognized by him. Among cultural values, there is respect for clerics, admiration for the Hausa court, accepting patriarchal model of the society and low social status of women. Abubakar Imam’s sense of humour and his feeling for language complement the features that determine the author’s style and narrative features of the book.